PENYEBARAN Ficusspp DI HUTAN GUNUNG TUMPA, PROVINSI SULAWESI UTARA. - Abanius Yanengga; Martina A. Langi; Reinold P. Kainde; Wawan Nurmawan (Universitas Sam Ratulangi, 2015)
ABSTRACTTumpa Mountain area in North Sulawesi province was originally aprotected forest that isseton 28 April 1932 wide 215 ha, then based SK. 434/Menhut-II/2013 On June 17, 2013 the status of the switch into Forest Park (TAHURA) with extensive 296 ha. The purpose of this research to study the spread of Ficus groups in forest areas of Mount Tumpa, North Sulawesi. The method used in this research is the exploration method to divide the study area based on the direction of the wind, namely; aspecteast, west, north, and south. In every aspect of the slope was observed distribution of the types of groups Ficus. The data is then compiled and tabulated gotten based aspects of the slope and level/phasegrows. The results of the research that has been done there is 230 individuals Ficus spp. Spread in 9 types. Based on Ficus spp aspect, is the most dominant aspect of the West (85) followed aspect, further deployment based on the level of growth is the level of the tree(112) followed by the pole (53) individuals